Protective Effects of Ethanol Tuber Extract of (Tigernut) C. Esculentus against Arsenic Trioxide-Induced Cardiotoxicity in Wistar Rats - S. B. Olukayode; S. O. Innih; G. I. Eze (Journal of Applied Sciences and Environmental Management)
Therefore, the objective of this paper is to investigate the protective effects of ethanol tuber extract of (Tigernut) C. esculentus (ETECE) against Arsenic Trioxide (ATO)-induced cardiotoxicity in Wistar rats using appropriate standard procedures. Histological examination revealed that ATO exposure led to severe cardiac damage, characterized by coronary vascular ulceration, interstitial congestion, perivascular myocardial degeneration, and perivascular fibrosis. However, treatment with escalating doses of ETECE and vitamin C resulted in mild attenuation of these effects. Notably, the 200 mg/kg body weight dose of ETECE demonstrated a comparable protective effect to that of vitamin C. In summary, ETECE exhibited a moderate mitigating effect against ATO-induced cardiotoxicity, indicating that while ETECE may offer some level of cardioprotection, it is unlikely to be a complete safeguard against ATO-induced cardiac damage.